Classification of the harmonic load types using Multi-Layer Extreme Learning Machine - Wong S.Y.; Yap K.S.; Li X. (Institution of Engineering and Technology, 2023)
Aggregates; Classification (of information); Electric power systems; Harmonic analysis; Knowledge acquisition; Learning systems; Auto encoders; Classification results; Electricity consumers; Extreme learning machine; Harmonic loads; Load characteristics; Power system; Power system applications; Electric power system planning